Exercise induced bronchoconstriction and sports. Issue 996 (18th November 2008) - Billen, A; Dupont, L
Abstract : Exercise induced bronchoconstriction (EIB) describes the acute transient airway narrowing that occurs during and most often after exercise, and is prevalent in elite athletes. Prolonged hyperventilation of dry or cold air and increased inhalation of pollutants or allergens could account for the bronchoconstrictive reaction. The subsequent airway inflammation seems to differ from typical asthma. Objective measures of lung function and provocation tests should be used for an accurate and reliable diagnosis. EIB is currently treated with inhalation of β2 -agonists or, as second choice, sodium cromoglycate approximately 15 min before exercise. If this proves to be insufficient then inhaled steroids should be added. Leukotriene receptor antagonists can be used in patients whose symptoms do not respond to inhaled steroids. The screening of high risk populations such as swimmers, cyclists, rowers and winter athletes is recommended by some authors. Drug doping regulations and practical recommendations for competitive athletes and their health care providers are explained.